The Bedrock Topography Deduced from Multiple Radar Echoes Observed in the Mizuho Plateau, East Antarctica - Shinji MAE (National Institute of Polar Research, 1978)
Taking into account the effect of spatial fading and erronous echoes caused by large scale undulations of bedrock surface, the radar echo data by the 14th Japanese Antarctic Research Expedition were reanalysed to obtain the ice thickness and bedrock topography in the Mizuho Plateau area. The bedrock topographies along three Routes A, C and S are drawn by solid lines in Figs. 3, 4 and 5 respectively. Even though slopes on the bedrock were smoothened, there remain some steep ones which satisfy the condition of the existence of a sub-ice water lake. Since it was expected from the data of surface velocity measurements along Route A that the basal sliding was taking placing with the ice sheet north of Route A in the Mizuho Plateau, it is probable that there exist a sub-ice water lake along the valley indicated by a dotted line V-W in Fig. 2.